2006
DOI: 10.1017/s0265021506000603
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of influence of sevoflurane on the reactivity of microglial cells in the course of the experimental model of intracerebral haemorrhage

Abstract: Administration of sevoflurane during anaesthesia in animals with intracerebral haemorrhage evoked a decrease of activation of the microglial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Our data show that after IR injury, microglia were rapidly activated in IR group rats, as cells were intensely stained with Iba-1 antibody and possessed enlarged and vacuolated cell bodies extending stout processes (Figure 4A). Sevoflurane preconditioning markedly prevented increases in Iba-1 protein expression (Figure 5A), completely consistent with the results of Karwacki Z and colleagues [30]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data show that after IR injury, microglia were rapidly activated in IR group rats, as cells were intensely stained with Iba-1 antibody and possessed enlarged and vacuolated cell bodies extending stout processes (Figure 4A). Sevoflurane preconditioning markedly prevented increases in Iba-1 protein expression (Figure 5A), completely consistent with the results of Karwacki Z and colleagues [30]. …”
Section: Discussionsupporting
confidence: 91%
“…Karwacki Z and colleagues reported that sevoflurane in concentrations of 1 and 2 MAC (minimum alveolar concentration) inhibited ischemia-induced polymorphonuclear neutrophil (PMN) adhesion. With similar immunophenotypical features as those of PMN, sevoflurane was demonstrated to modulate microglial adhesion [30]. Herein, we used Iba-1 as cellular marker of microglia and analyzed microglial activation qualitatively and quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…The control group comprised of animals that underwent the same surgical procedure as rats that were subjected to intracerebral haematoma (described below) with the exception of blood injection. In the study we used the experimental model of intracerebral haemorrhage described previously by Karwacki et al [15][16][17] where detailed description of anaesthetic and surgical procedures were presented. Here we provide brief description of the experimental procedures used.…”
Section: Animal Proceduresmentioning
confidence: 99%
“…Temperature commonly decreases following anesthesia in small animals, principally due to their high surface area-to-body mass ratio making thermo- Harvey and Paddleford, 1993;Karwacki et al, 2005Karwacki et al, , 2006aKiyatkin and Brown, 2005. regulation difficult. The use of unwarmed anesthetic gases exacerbates this problem (Haskins and Patz, 1980).…”
Section: Minimizing Excess Inflammationmentioning
confidence: 99%